Understanding the principalship : an international guide to principal preparation - Slater, Charles L.; Nelson, Sarah W. (Advances in educational administration, 2013)
This volume originates from the International study of principal preparation (ISPP), a collaborative project representing nearly a decade of research on principal preparation in countries throughout the world. Through focused stages of research, the ISPP systematically examined the kinds of preparation available to principals and how this preparation serves principals in their first years in the post. The authors attend to dynamic changes that are affecting the way principals work. Demographic shifts, globalization, and emerging technologies are transforming the world and the role of educational leaders. Economic and political forces are causing waves of migration from one country to another. Even within the same country, changes in labour markets and political turmoil are pushing people into new communities. The authors provide extensive reviews of literature on educational administrator preparation and also offer a perspective on local history and culture. They develop an intercultural approach to understanding the principalship and to highlight marginalized and underrepresented groups.